2018
DOI: 10.14444/5078
|View full text |Cite
|
Sign up to set email alerts
|

Arm Pain Versus Neck Pain: A Novel Ratio as a Predictor of Post-Operative Clinical Outcomes in Cervical Radiculopathy Patients

Abstract: Background: Informed patient selection and counseling is key in improving surgical outcomes. Understanding the impact that certain baseline variables can have on postoperative outcomes is essential in optimizing treatment for certain symptoms, such as radiculopathy from cervical spine pathologies. The aim was to identify baseline characteristics that were related to improved or worsened postoperative outcomes for patients undergoing surgery for cervical spine radiculopathic pain. Methods: Retrospective review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 41 publications
7
24
1
Order By: Relevance
“…in addition, using both methods, multivariate analysis revealed that having aPD symptoms (being in the a group or aPD group) was an independent predictor of improvement in nDi (P = 0.049 and P = 0.020, respectively). these results are similar to a recently published retrospective study by Passias et al 17 the authors of that study noted that arm pain greater than neck pain at baseline was associated with increased odds of arm pain improvement and PCS scores after surgery. in addition, a higher baseline nDi score was associated with reduced odds of improvement in neck pain postoperatively.…”
Section: Discussionsupporting
confidence: 91%
“…in addition, using both methods, multivariate analysis revealed that having aPD symptoms (being in the a group or aPD group) was an independent predictor of improvement in nDi (P = 0.049 and P = 0.020, respectively). these results are similar to a recently published retrospective study by Passias et al 17 the authors of that study noted that arm pain greater than neck pain at baseline was associated with increased odds of arm pain improvement and PCS scores after surgery. in addition, a higher baseline nDi score was associated with reduced odds of improvement in neck pain postoperatively.…”
Section: Discussionsupporting
confidence: 91%
“…Reduction in levels of neck and arm pain has been thought to be important factors influencing the recovery of disability in individuals with CR (Engquist et al, ; Passias et al, ). However, the reduction in neck and arm pain explained only a third of the influence of self‐efficacy on the recovery of disability.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these analytic methods have been previously applied in the cervical spine, but not in the lumbar spine. 16,17…”
Section: Study Design and Patient Outcomesmentioning
confidence: 99%